Conformed to gender conformity? Gender nonconformity stigma is buffered by personal contact - Rodrigues, D. L. (Journal of Social and Personal Relationships, 2025)
Research has shown that individuals from sexual and gender minorities are more likely to be stigmatized. Taking the perceiver’s perspective, we conducted two experimental studies to examine gender nonconformity stigma and the conditions under which such stigma is more (or less) likely to emerge. In both studies, participants were asked to read descriptions of targets varying in gender (non)conformity and assigned sex (Study 1; N = 337) or sexual identity (Study 2; N = 406). Results from both studies showed that participants preferred more social distance from gender nonconforming (vs. conforming) targets, tended to dehumanize them (i.e., attributed them more primary and less secondary emotions), and reported less anti-violence behavioral intentions and justifications. In both studies, results further showed that having more frequent and positive personal contact with gender nonconforming individuals helps buffer against gender nonconformity bias. Unexpectedly, results from Study 2 showed that humanizing gender nonconforming targets (rather than dehumanizing them) was associated with more violence predispositions for participants who reported having more negative personal contact with gender nonconforming individuals. No differences were found according to the targets’ assigned sex or sexual identity. Taken together, our findings highlight the need to understand the causes and boundaries of gender nonconformity bias.